An Evaluation of the Rabies Surveillance in Southern Vietnam - Pham, Quang Duy; Phan, Lan Trong; Nguyen, Thuy Phuong Thi; Doan, Quan Minh Ngoc; Nguyen, Hai Duc; Luong, Quang Chan; Nguyen, Thuong Vu (Frontiers in Public Health, 2021)
Introduction: Rabies is endemic in Vietnam and has been a statutory notifiable infectious disease since 1998. We, herein, assessed the performance of rabies surveillance in Southern Vietnam and identified areas for improvement. Materials and Methods: We analyzed data on human rabies cases reported during 1991–2018. We adapted guidelines from the U.S. Centers for Disease Control and Prevention to evaluate attributes of surveillance. Between June and November 2018, we interviewed a total of 145 staff from hospitals, preventive medicine centers, and animal health offices at provincial and district levels in five southern provinces. Results: Between 2009 and 2018, an average of nine cases of human rabies (range: 4–20 cases) was reported annually in Southern Vietnam, representing an incidence of 2.7 cases per 10 million population. The highest incidence was observed in 2018 (5.5 cases per 10 million population). Survey data suggested that only 24% (13/53) of participants agreed that the monthly report template was easy to complete and that 42% (23/55) indicated that the change from the paper-based to the electronic case notification systems was easy. Only 7% (2/29) of human rabies cases were reported timely, and 65% (13/20) successfully collected specimens. Approximately 39% (56/144) of staff were aware of turning surveillance data into prevention activities, and 21% (31/145) witnessed data used for strategic program decision making. Conclusions: Although rabies surveillance was quite simple, flexible, and accepted in southern Vietnam, simplifying the report forms, training staff, and improving the timeliness of reporting and data usage are highly recommended for a better implementation of rabies surveillance.